Rendering wrought aluminium alloys castable by means of minimum composition adjustments. (4th July 2017) - Koutsoukis, Theodoros; Makhlouf, Makhlouf M.
Abstract: Wrought alloys have low fluidity and are prone to hot tearing, which make them difficult to cast. The presence of eutectic-forming elements in the alloy composition lessens these effects. For this reason, the constituents of casting alloys tend to include a eutectic portion. Typically, silicon is added to aluminium alloys to provide casting ability by forming the aluminium–silicon eutectic. However, the presence of silicon in aluminium alloys is associated with a number of issues that do not allow these alloys to reach their full potential. In this publication we report results of our investigation of three alternative eutectics: Al–6.1Ni, Al–1.8Fe, and Al–1.75Fe–1.25Ni. Our results indicate that these eutectics have satisfactory fluidity and resistance to hot tearing and higher strength than the aluminium–silicon eutectic. We also found that introducing these eutectic compositions into 7075 wrought alloy results in a castable composition with yield strength comparable to that of the wrought alloy.